Polarization of Vδ2 T cells to a Th2-like phenotype promotes plasmablast differentiation and possesses pro-fibrotic properties in IgG4-related disease - Li, Jieqiong; Wang, Mu; Zhou, Jiaxin; Fei, Yunyun; Li, Mengtao; Zhao, Yan; Zeng, Xiaofeng; Peng, Linyi; Zhang, Wen (Frontiers in Immunology, 2025)
ObjectivesTo explore the phenotype and role of gamma delta (γδ) T cells in the pathogenesis of IgG4-related disease (IgG4-RD).MethodsFlow cytometry and quantitative RT-PCR were employed to analyze γδ T cell subsets, chemokine receptor expression, cytokine production, pro-fibrotic gene expression, and transcription factor profiles. Immunofluorescence assessed Vδ2 T cell infiltration in affected tissues. Chemotaxis assays and co-culture experiments investigated Vδ2 T cell migration and their influence on B cell differentiation. The impact of IL-21 stimulation and JAK/STAT3 inhibitors on γδ T cell was also evaluated.ResultsPatients with IgG4-RD exhibited decreased peripheral Vδ2 T cells displaying a Th2-like phenotype characterized by elevated Th2 cytokine production and activated IL-21—STAT3—Blimp-1—GATA3 pathway. Vδ2 T cells accumulated in affected tissues through CCR7 upregulation, and co-localizing with B cells. Both Vδ2 T cells and culture supernatants from IgG4-RD patients promoted B cell differentiation. IL-21 stimulation augmented pSTAT3, Blimp-1, and GATA3 expression in Vδ2 T cells, while JAK and STAT3 inhibitors attenuated these effects. IgG4-RD patients exhibited increased TGF-β and pro-fibrotic gene expression in γδ T cells.ConclusionWithin the IL-21-rich microenvironment of IgG4-RD, peripheral Vδ2 T cells acquire a Th2-like phenotype via the IL-21—STAT3—Blimp-1—GATA3 pathway. Targeting JAK/STAT3 inhibitors holds therapeutic potential for IgG4-RD.